Firefly algorithm technique for solving economic dispatch problem - Mohd Herwan, Sulaiman, Dr.; Mohd Wazir, Mustafa, Prof. Dr.; Zetty Nurazlinda, Zakaria; Omar, Aliman; Siti Rafidah, Abdul Rahim (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/